Exploring the Impact of Video and Poster Media on Leprosy Education: a Study on Instagram - Siswahyuni, Zulaika; Cahyanti, Anindya Disetya; Rifanti, Dinda Putri (Tarqabin Nusantara Group, 2024)
Introduction: Leprosy is a chronic infectious disease caused by Mycobacterium leprae that causes damage to the peripheral nerves. Leprosy prevalence data in Indonesia in 2020-2022 did not increase significantly. So secondary prevention is needed to minimize disability because the disability rate of leprosy in Indonesia is high. Methods: Health promotion activities regarding leprosy were carried out by making posters and educational videos related to leprosy and uploaded on Instagram. This activity was carried out by Public Health Science students offering B State University of Malang online through the Instagram account @komkes.ikmb22. Results: There is a significant difference in insight from health promotion media using videos and posters. The use of video media is preferred and reshared by the public compared to posters. Factors that support video health promotion media are preferred by the public because of the presence of images and sound so that it creates interest in learning and knowing information. Conclusion: video media is preferred than poster media because there are images and sounds that play at one time so that the audience is more interested in seeing and watching it and the information is easy to understand.